Trap Assisted Dynamic Mechanoluminescence Toward Self‐Referencing and Visualized Strain Sensing - Tianli Wang; Pengfei Zhang; Jianqiang Xiao; Ziyi Guo; Xiongwu Xie; Jiahao Huang; Jiaojiao Zheng; Xuhui Xu; Lei Zhao (Advanced Science)
Abstract Strain sensors utilizing mechanoluminescent (ML) materials have garnered significant attention and application due to their advantages, such as self‐powering, non‐contact operation, and real‐time response. However, ML‐based strain sensing techniques typically rely on the establishing of a mathematical relationship between ML intensity and mechanical parameters. The absolute ML intensity is vulnerable to environmental factors, which can result in measurement errors. Herein, an color‐resolved visualized dynamic ML and self‐referencing strain sensing is investigated in Ca9Al(PO4)7: Tb3+, Mn2+. By analyzing the ML performance under various mechanical stimulations and adjustable strain parameters, a relationship between strain and the ML intensity ratio of Tb3+/Mn2+ is aimed to bed established. This will enable the development of a self‐referencing and visualized strain sensing technology. Through a comparison of luminescence characteristics under continuous mechanical stimulation (stretching) and continuous X‐ray irradiation, it is discovered that the ratiometric dynamic ML is primarily driven by the dynamic filling and continuous release of carriers form traps, which compensates for the ML of Mn2+. Leveraging the self‐referencing and color‐resolved (from green to red) visualized ML characteristics, an application scenario for monitoring human joint movement is developed. This approach offers new insights into the use of dynamic ML materials in strain sensing and human‐machine interaction.